1979
DOI: 10.1111/j.1365-2621.1979.tb10049.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive Quality of Fermented Cowpeas (Vigna Sinensis) and Chickpeas (Cicer Arietinum)

Abstract: Cowpeas and chickpeas were allowed to undergo natural fermentation for 4 days at 25°C. The microorganisms isolated from cowpeas and chickpeas were Lactobacillus casei, L. leichmanii, L.plantarum, Pediococcus pentosaceus and P. acidilactici. Lactobacillus helveticus was found in chickpeas only. This makes the fermentation chiefly lactic acid. Pathogenic organisms were not found in the system. Relative nutritive value (RNV) and limiting amino acids increased significantly (P < 0.05) in the fermented beans. Niaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 9 publications
2
35
0
1
Order By: Relevance
“…The knowledge that conjugated forms have less biological effect than aglycones has stimulated the development of technological processes to obtain soybean products rich in isofl avone aglycones by different treatments such as addition of enzymes or by the action Fermentation is an ancient technology that remains one of the most practical methods for enhancing the nutritional and organoleptic qualities of foods. It has been reported that the fermentation causes a general improvement in the nutritional value of legumes [Zamora & Fields, 1979;Akpapunam & Achinewhu, 1985]. In general, fermentation of legumes leads to an improvement in their nutritional value, such as in protein quality, increased palatability, increased levels of B vitamins [Frías et al, 1996;Granito et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge that conjugated forms have less biological effect than aglycones has stimulated the development of technological processes to obtain soybean products rich in isofl avone aglycones by different treatments such as addition of enzymes or by the action Fermentation is an ancient technology that remains one of the most practical methods for enhancing the nutritional and organoleptic qualities of foods. It has been reported that the fermentation causes a general improvement in the nutritional value of legumes [Zamora & Fields, 1979;Akpapunam & Achinewhu, 1985]. In general, fermentation of legumes leads to an improvement in their nutritional value, such as in protein quality, increased palatability, increased levels of B vitamins [Frías et al, 1996;Granito et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Ce résultat corrobore les étu-des de Zamora et Fields (1979). L'amélio-ration de la digestibilité proviendrait d'une part de la disponibilité de l'amidon vis à vis des enzymes (Cronk et al 1977) et d'autre part de l'élimination des inhibiteurs de l'amylase que sont les phytates et les polyphénols (Thompson et Yoon, 1984 (Brou, 2000), l'amidon résistant et les fibres contribueraient à développer les flatulences (Champ et al, 1990).…”
Section: Discussionunclassified
“…Total soluble solids (TSS) measurements were carried out using hand refractometers (Atago Co., Ltd., Tokyo, Japan). Titratable acidity (TA), expressed as tartaric acid, was determined by titration 0.1 mol equivalent/L NaOH to pH 8.1 (Zamora & Fields, 1979). The reducing sugar and total sugar of each sample were determined according to the AOAC (1995) procedures.…”
Section: Methodsmentioning
confidence: 99%